Analisis dan Rekayasa Ulang Proses Bisnis Sistem Pembelian pada PT XYZ - Agus Sulaiman (Universitas Multimedia Nusantara, 2014)
In this modern era, business processes become one of the important aspects for a company to stay ahead in the competition to its competitors. A company that has an optimal business processes and supported by an integrated information system will win the competition. This study aims to optimize the purchasing business process of Company XYZ using the concept of Business Process Re-engineering (BPR) approach as the basis for designing the next module of enterprise information systems. From this study, we found that there are still business processes that need to be revised and improved to integrate the flow of data and information from one department to another department. Business process that needs to be revised is an overseas purchase; Business processes that need to be improved are Overdelivery and Under-delivery Tolerance, PO Free Goods, PO Subcontracting, and Purchasing Planning consisting of Weekly Projected Sales, Weekly Order Projection & Daily Order Projection. Index Terms - Business Process Reengineering, Business Process Purchasing.